Changes in import pricing behaviour: the case of Germany - Kerstin Stahn (Deutsche Bundesbank, 2009)
Since changes in import prices feed into consumer prices and thus might affect monetary policy decisions, policymakers need to establish whether or not German importers' long-run pricing behaviour has changed. Of particular interest are any shifts in the importance of cost passthrough and pricing-to-market for import pricing in Germany that may have ocurred since the 1990s. We analyse pricing in single equations for 11 product categories because the factors influencing the pricing behaviour, eg competitive pressure, may well have developed differently on the individual product markets. The Saikkonen (1991) approach is applied to test the import price levels for changes in the impact of their determinants. After aggregating the findings for the individual product categories, we find that, on the whole, pricing-to-market has increased, whereas cost pass-through via foreign costs and exchange rates is lower, but not via commodity prices.
Keywords: 330; import pricing; cost pass-through; exchange rate pass-through; pricing-to-market; Germany; Außenhandelspreis; Exchange Rate Pass-Through; Kosten; Betriebliche Preispolitik; Deutschland; pricing to market